2015
DOI: 10.1007/s10762-014-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Miniature Incandescent Light Bulbs for Thermal Infrared ‘THz Torch’ Applications

Abstract: The 'THz Torch' concept is an emerging technology that was recently introduced by the authors for implementing secure wireless communications over short distances within the thermal infrared (20-100 THz, 15 μm to 3 μm). In order to predict the band-limited output radiated power from 'THz Torch' transmitters, for the first time, this paper reports on a detailed investigation into the radiation mechanisms associated with the basic thermal transducer. We demonstrate how both primary and secondary sources of radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Moreover, having glass envelopes (e.g. with the miniature COTS incandescent light bulbs used in our earlier proof-of-concept demonstrators), the output radiated power is significantly reduced because of the high absorption of the window glass below ∼65 THz [12]. For these reasons, more efficient but also more expensive miniature COTS thermal emitters can be used.…”
Section: Increased Channel Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, having glass envelopes (e.g. with the miniature COTS incandescent light bulbs used in our earlier proof-of-concept demonstrators), the output radiated power is significantly reduced because of the high absorption of the window glass below ∼65 THz [12]. For these reasons, more efficient but also more expensive miniature COTS thermal emitters can be used.…”
Section: Increased Channel Densitymentioning
confidence: 99%
“…This offers opportunities for developing such systems within this largely unregulated part of the electromagnetic spectrum. The 'THz Torch' concept was recently introduced by the authors for providing secure wireless communications over short distances within the thermal infrared [8][9][10][11][12][13]. Both single-and multi-channel wireless links have been reported; the resilience to interception and jamming with 2.56 kbps frequency division multiplexing (FDM) and 0.64 kbps frequency-hopping spread-spectrum (FHSS) systems has been demonstrated experimentally [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4. It should be noted that when the total effective radiating areas of A e f f À filament and A e f f À glass are taken into account for the filament and glass envelope, respectively, the resulting radiant intensities are of the same order of magnitude from the two sources of radiation [7]. Furthermore, it is clearly shown that at a bias current of 44 mA, Channel A, C and D are expected to have higher output radiated power, as the spectral radiance peaks locate within the pass bands of their respective filters at this bias point.…”
Section: Transmitter Output Radiant Intensitymentioning
confidence: 99%
“…On the other hand, Channel B is away from either radiation peaks, giving the lowest output radiated power of the four channels, as will be confirmed experimentally in Section 5. [28] and calculated net spectral radiance from both primary and secondary radiation at a bias current of 44 mA [7] 4 Free space losses…”
Section: Transmitter Output Radiant Intensitymentioning
confidence: 99%